Penerapan Metode Concept Song dalam Peningkatan Pemahaman pada Mata Pelajaran Al-Qur’an Hadits Siswa di MTs Yapika Petanahan Kebumen - Ika Kurniasih; Rifqi Aulia Rahman; Noor Aziz (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This thesis aims to: 1) find out the reality of students' understanding of the Al-Qur'an Hadith subject at MTs Yapika Petanhan Kebumen, 2) find out the application of the concept song method in improving students' understanding of the Al-Qur'an Hadith subject at MTs Yapika Petanahan Kebumen, 3) find out the contribution of the concept song method to improving students' understanding of the Al-Qur'an Hadith subject at MTs Yapika Petanahan Kebumen. The results of the study indicate that: 1) The reality of students' understanding of the Al-Qur'an Hadith subject at MTs Yapika Petanhan Kebumen, Teacher planning in the Al-Qur'an Hadith learning process, Teacher implementation in the Al-Qur'an Hadith learning process, Student responses to learning the Al-Qur'an Hadith 2) Application of the concept song method in improving students' understanding of the Al-Qur'an Hadith subject at MTs Yapika Petanahan Kebumen, The process of applying the Concept song method, Student responses to the application of the methodconcept song, 3) Contribution Application of the concept song method in improving students' understanding of the Al-Qur'an Hadith subject at MTs Yapika Petanan. Obstacles in the application of the concept song methodconcept song, Method contributionconcept song, Students' understanding of the concept song method.